Satellite image resolution enhancement using discrete wavelet transform and new edge-directed interpolation - Witwit, Wasnaa; Zhao, Yifan; Jenkins, Karl W.; Zhao, Yitian (Society of Photo-Optical Instrumentation Engineers (SPIE), 2017)
An image resolution enhancement approach based on discrete wavelet transform (DWT) and new edge-directed interpolation (NEDI) for degraded satellite images by geometric distortion to correct the errors in image geometry and recover the edge details of directional high-frequency subbands is proposed. The observed image is decomposed into four frequency subbands through DWT, and then the three high-frequency subbands and the observed image are processed with NEDI. To better preserve the edges and remove potential noise in the estimated high-frequency subbands, an adaptive threshold is applied to process the estimated wavelet coefficients. Finally, the enhanced image is reconstructed by applying inverse DWT. Four criteria are introduced, aiming to better assess the overall performance of the proposed approach for different types of satellite images. A public satellite images data set is selected for the validation purpose. The visual and quantitative results show the superiority of the proposed approach over the conventional and state-of-the-art image resolution enhancement.
Keywords: discrete wavelet transform; new edge-directed interpolation; image resolution enhancement; satellite image; geometric distortion; super-resolution